Accurate prediction of the needle depth required for successful lumbar puncture - Chong, S.Y.; Chong, L.A.; Ariffin, H. (Elsevier, 2010)
Introduction: The aim of this study is to formulate an accurate estimate of the spinal needle depth for a successful lumbar puncture in pediatric patients. Methods: This is a prospective study of pediatric oncology patients who had lumbar punctures in the course of their treatment. The distance from skin entry point to the tip of the spinal needle was measured after lumbar punctures were performed. The relationship between the depth of needle insertion with weight, height, body surface area, body mass index, intervertebral space used, ethnicity, and sex of patient were studied. Predictive statistical models were used for the formulation of the ideal lumbar puncture needle depth. Results: Two hundred seventy-nine patients who had nontraumatic lumbar punctures were studied. The patient characteristics were as follows: age, 0.5 to 15 years; weight, 7 to 63 kg; and height, 70 to 162 cm. Analysis using multiple regression tests with stepwise approach showed a strong relationship between the lumbar puncture needle depth and weight/height ratio. By using a predictive regression model, ideal depth of needle insertion (cm) = 10 [weight(kg)/height(cm)] + 1, with a regression coefficient r = 0.77. Conclusion: This formula is accurate and practical with less complex calculations. However, further validation in a prospective study will be needed. (C) 2010 Published by Elsevier Inc.